Radiofrequency therapy for severe idiopathic vulvodynia - Kestřánek, Jan; Špaček, Jiri; Ryška, Pavel; Adamkov, Jaroslav; Matula, Vojtech; Buchta, Vladimir (Journal of lower genital tract disease, 2013)
OBJECTIVE: The study aimed to provide a description of a new and a hopeful possibility in the treatment of severe vulvodynia, which does not respond to treatments used so far. MATERIALS AND METHODS: The use of radiofrequency therapy in vulvodynia treatment is described for the first time. This method was suggested by a neurosurgeon after applying all available possibilities. RESULT: In this article, we are reporting on the successful use of the pulsed radiofrequency treatment in a patient with intractable chronic vulvodynia. CONCLUSIONS: To our knowledge, this is the first report of a successful use of pulsed radiofrequency in the treatment of chronic vulvodynia. If efficacy of pulsed radiofrequency is confirmed by more studies, it would be a welcome addition to the treatment modalities used to treat this sometimes truly intractable condition.
Keywords: Pulsed Radiofrequency Treatment; pulsní radiofrekvenční terapie; lidé; Chronic Disease; chronická nemoc; výsledek terapie; ženské pohlaví; lidé středního věku; Humans; Middle Aged; Treatment Outcome; Vulvodynia; Female; vulvodynie